Hostel Online Leave Form System for the Students Leave Requests - Bhatlavande, Amey; Galgunde, Sanika; Kshirsagar, Pratiksha; Wadkar, Sanskruti (International Journal of Computer Sciences and Engineering, 2024)
The "Hostel Online Leave Form System" is a digital platform developed using Android and Java, specifically designed to streamline the management of student leave requests within educational institutions. This innovative system features a user-friendly interface that enables students to submit leave applications electronically, significantly reducing the reliance on manual paperwork and enhancing overall administrative efficiency. By utilizing Firebase as its database, the platform automates the leave management process, facilitating structured approval workflows involving multiple authorities, including hostel wardens and administrative personnel.Each leave request undergoes a thorough review at various stages, ensuring transparent and informed decision-making. This multi-level approval system allows for careful scrutiny of each application, fostering accountability among administrators. Real-time updates and notifications keep both students and administrators informed about the status of leave applications, effectively minimizing delays and reducing instances of miscommunication. By leveraging modern technology, the Hostel Online Leave Form System not only improves the user experience for both students and staff but also enhances the tracking and management of leave data. The system allows for accurate record-keeping, enabling authorities to analyze trends over time and make data-driven decisions. Features such as a user-friendly dashboard provide administrators with insights into key metrics related to leave management, making it easier to identify patterns and address potential issues.